2019
DOI: 10.1021/acs.macromol.9b01705
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Long-Chain Branched Polyolefins by Coordinative Chain Transfer Polymerization

Abstract: Synthesis of long-chain branched polymers has been a crucial concern in the polyolefin industry. In this study, a method to produce long-chain branches (LCBs) in coordinative chain transfer copolymerization (CCTcoP) is suggested. A dialkylzinc compound bearing vinyl groups ((9-decenyl)2Zn) is prepared, which works well not only as a chain transfer agent but also as a comonomer in CCTcoP, resulting in the generation of LCBs. The generation of LCBs is confirmed by gel permeation chromatography studies and throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…The yields were satisfactorily high (60%-68%). The same treatment of the ligand carrying an ethyl substituent (17) did not afford the desired complexes. However, the desired complex (23) was obtained in high yield (65%) when 17 was treated with HfMe 4 generated in situ in the reaction of HfCl 4 with 4 eq of MeMgBr at −35 • C [51].…”
Section: Preparation Of Hf Complexesmentioning
confidence: 93%
See 1 more Smart Citation
“…The yields were satisfactorily high (60%-68%). The same treatment of the ligand carrying an ethyl substituent (17) did not afford the desired complexes. However, the desired complex (23) was obtained in high yield (65%) when 17 was treated with HfMe 4 generated in situ in the reaction of HfCl 4 with 4 eq of MeMgBr at −35 • C [51].…”
Section: Preparation Of Hf Complexesmentioning
confidence: 93%
“…In living olefin polymerization, only one polymer chain is limitedly grown per a molecule of catalyst. A practical and commercially relevant method-coordinative chain transfer polymerization (CCTP)-has been developed, in which chain transfer agents (e.g., Et 2 Zn) are deliberately added in excess relative to I (e.g., [Zn]/[Hf] > 100) [15][16][17]. A rapid alkyl exchange between the chain-growing Hf center and chain transfer agent Zn sites results in transformation of the fed Et 2 Zn to (polyolefinyl) 2 Zn.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 1 is capable of incorporating a significant amount of α-olefins in an ethylene/α-olefin copolymerization [47]. A minimal amount of MMAO (50 µmol-Al) had to be fed, in addition to the CTA (1-hexyl)2Zn (100 or 200 µmol-Al), to realize the full activity of 1, even though PO chain growth from some Al-sites was unavoidable [26,48,49]. The generated (polyolefinyl)2Zn was treated with t- In contrast, we found that (tBu) 2 Zn was decomposed at 130 • C, and a black solid precipitated when a solution of (tBu) 2 Zn in decane was heated at 130 • C. Isobutene and H 2 signals were detected in the 1 H NMR spectrum when the reaction was performed in a sealed tube in toluene-d 8 (Scheme 2b).…”
Section: Attempts To Synthesize Block Copolymersmentioning
confidence: 99%
“…Moreover, 1 is capable of incorporating a significant amount of α-olefins in an ethylene/α-olefin copolymerization [47]. A minimal amount of MMAO (50 µmol-Al) had to be fed, in addition to the CTA (1-hexyl) 2 Zn (100 or 200 µmol-Al), to realize the full activity of 1, even though PO chain growth from some Al-sites was unavoidable [26,48,49]. The generated (polyolefinyl) 2 Zn was treated with t-BuLi (…”
Section: Attempts To Synthesize Block Copolymersmentioning
confidence: 99%
“…[6][7][8][9] Generally, in order to improve the melt strength of poly-olen, a great deal of effort has been devoted to introducing long-chain branches and hydrogen bonds into the polymer network. [10][11][12][13] Li et al [14][15][16] graed the long-chain monomer glycidyl methacrylate onto the PP molecular chain to improve the melt strength of PP, while improving its crystallization performance and toughness; Yoshii et al [17][18][19][20] prepared high-meltstrength PP (HMSPP) by adding multifunctional monomers using an electron beam and g-ray irradiation methods. However, the network structure formed by introducing long branches is easy to cross-link, and so is difficult to reuse.…”
Section: Introductionmentioning
confidence: 99%